Simultaneous atrial and ventricular restitution and fibrillation analyses using a low-cost scalable panoramic whole-heart optical mapping configuration for whole-heart imaging of translational models. (14th October 2021) - Calvo, C J; Zarzoso, M; Guill, A; Tormos, A; Such, L; Alberola, A; Millet, J; Chorro-Gasco, F J
Abstract: Introduction: Optical mapping (OM) is the primary method for imaging electrophysiologically relevant parameters from the outer surface of Langendorff-perfused hearts. However, current panoramic OM systems are financially challenging, require multiple sensors to map wide areas of the surface with overlapping regions and missing areas of interest due to the intrinsic shape of the heart. We proposed different panoramic configurations to dynamically characterize atrial and ventricular function during arrhythmia and, in presence of a coronary occlusion. Methods: We devised both a multi-sensor and a single sensor system integrated with the perfusion circuit comprising sensor elements, a control system for led illumination, electrical stimulation and sensing of physiological variables. Two configurations were tested: A multi-sensor panoramic approach including different camera views and, a precision near-ellipsoidal curved mirror (highly concentrated reflectance in the range 380nm-800nm), with exponential profile and diameter to harbor small to large hearts was used. Twelve-rabbits and two pig hearts were included in the study. OM was performed using di-4 ANDBQPQ near-infrared dye and 5–10uM blebbistatine. Initial camera calibration was done using a fishnet-like pattern and nylon landmarks. We characterized signal-tonoise ratios (SNR) of reconstructed action potentials (AP) and obtained parametric maps of the activation process. A custom-built computational pipeline for accurate motion compensation and AP reconstructions was used. Hearts were stimulated until ventricular fibrillation (VF) was induced with and without presence of a coronary occlusion in the LADartery (LADCO). Results: High SNRs spatial maps were obtained after AP reconstruction (42.24±4.23dB, stimulated; 23.31±5.24dB, VF) in the most restrictive set-up, the single-sensor near-ellipsoidal configuration. Quantified activation and repolarization dynamic restitution properties were assigned to anatomically labelled scale-invariant areas in the atrium and ventricles during the induction process. Atrial and ventricular restitution dynamics could be reconstructed and analyzed simultaneously. Slower conduction (CT) and higher dispersion in repolarization (DoR) was observed after LADCO in LV (CT: 13.4±5.31ms-vs-22.42±6.82ms, DoR:23.24±4.23ms-vs-38.03±9.17ms, p<0.05). During VF, more heterogeneous activation patterns, enhanced left-to-right VV spectral gradient profiles, and spatially constraint shorter-lived filaments, partially explained the disturbances observed during LADCO. Results obtained with a direct multiple sensor configuration allowed for complete tracking of dominant sources, yet presenting overlapped information. Conclusion: Hereby results comparing two low-cost configurations for panoramic imaging are presented and validated for the study of cardiac propagation throughout the whole epicardial surface for the study of arrhythmia, drug interventions and cardiovascular disease. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): CIBERcv